Desain Aplikasi Virtual Reality sebagai Upaya untuk Mengenalkan Sejarah Artefak Di Masjid Agung Demak - Yogananti, Auria; Hasyim, Noor (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2022)
The Great Mosque of Demak is one of evidence of Demak Kingdom in Indonesia that plays an important role in the spread of Islam in Java. The Great Mosque of Demak have a variety of objects and artifacts including four of main pillars from Walisongo, Pillars of Tatal, Dampar Kencana Majapahit, Bledheg doors, Candrasengkala at leading prayer place, pillar given by Majapahit on the porch of the mosque. All of these artifacts have unique history and stories told by generations. However, due to pop culture, those history and stories have begun to be forgotten mostly by teenagers in Demak. Design virtual reality application was created to provide information of artifacts so that it can attract the attention of Demak teenagers. The qualitative method is used with observation, interviews, documentation, and literature study. As for designing the virtual reality application using the Multimedia Development Life Circle (MDLC) method. This research produces a virtual reality application that contains history and stories of artifacts. Digitizing history and stories about artifacts have became one of the efforts to preserve the history and stories so it can remain to sustain especially for the youth community in Demak.